Synaptotoxic Signaling by Amyloid Beta Oligomers in Alzheimer's Disease Through Prion Protein and mGluR5 - Brody, A.H. (Adv Pharmacol, 2017)
Alzheimer's disease (AD) represents an impending global health crisis, yet the complexity of AD pathophysiology has so far precluded the development of any interventions to successfully slow or halt AD progression. It is clear that accumulation of Amyloid-beta (Aβ) peptide triggers progressive synapse loss to cause AD symptoms. Once initiated by Aβ, disease progression is complicated and accelerated by inflammation and by tau pathology. The recognition that Aβ peptide assumes multiple distinct states and that soluble oligomeric species (Aβo) are critical for synaptic damage is central to molecular understanding of AD. This knowledge has led to the identification of specific Aβo receptors, such as cellular prion protein (PrP(C)), mediating synaptic toxicity and neuronal dysfunction. The identification of PrP(C) as an Aβo receptor has illuminated an Aβo-induced signaling cascade involving mGluR5, Fyn, and Pyk2 that links Aβ and tau pathologies. This pathway provides novel potential therapeutic targets for disease-modifying AD therapy. Here, we discuss the methods by which several putative Aβo receptors were identified. We also offer an in-depth examination of the known molecular mechanisms believed to mediate Aβo-induced synaptic dysfunction, toxicity, and memory dysfunction.